Changes induced in the properties of dielectric silicone elastomers by the incorporation of transition metal complexes. (October 2016) - Stiubianu, George; Dumitriu, Ana-Maria Corina; Varganici, Cristian-Dragos; Tugui, Codrin; Iacob, Mihail; Bele, Adrian; Cazacu, Maria
Three new, cheap, and easily obtained complexes of triethanolamine with Cu(II), Ni(II), and Co(II) were incorporated in a high-molecular-weight polydimethylsiloxane-α, ω-diol (number-average molecular weight = 440, 000 g mol −1 ) together with silica nanoparticles. While silica has a well-known mechanical reinforcing role, adding the metal complexes with high dielectric permittivity aims to increase values for this characteristic of the prepared silicone composites in order to be useful for electromechanical applications. A simple procedure was employed for the incorporation of fillers by mechanical mixing in bulk without a solvent. The composites were processed as films and stabilized by curing initiated with 2, 4-dichlorobenzoyl peroxide at high temperature (180°C) and pressure. The cross-linking yield was estimated on the basis of swelling in chloroform, while the cross-linking density was calculated from differential scanning calorimetry traces. The filler's effect on mechanical and dielectric properties was assessed by appropriate measurements (tensile testing and dielectric spectroscopy). Changes in dielectric behavior as a result of the repeated deformation by stretching were also highlighted. Electromechanical sensitivity and ultimate tensile toughness values were estimated on the basis of these results as primary indices on suitability of these materials in transducers. The dielectric strength of the composite films was also evaluated by electrical breakdown field measurements.